Biosimilar granulocyte–colony‐stimulating factor for healthy donor stem cell mobilization: need we be afraid?. Issue 2 (26th June 2014) - Bonig, Halvard; Becker, Petra S.; Schwebig, Arnd; Turner, Matthew
<x xml:space="preserve">Abstract</x> Biosimilars are approved biologics with comparable quality, safety, and efficacy to a reference product. Unlike generics, which are chemically manufactured copies of small‐molecule drugs with relatively simple chemical structures, the biosimilar designation is applied to drugs that are produced by living organisms, implying much more difficult to control manufacturing and purification procedures. To account for these complexities, the European Medicines Agency (EMA), the US Food and Drug Administration, the Australian Therapeutic Goods Administration, and other regulatory authorities have devised and implemented specific, markedly more demanding pathways for the evaluation and approval of biosimilars. To date, several biosimilars have been approved, including versions of somatropin, erythropoietin, and granulocyte–colony‐stimulating factor (G‐CSF), and several biosimilar monoclonal antibodies are currently in development. The reference G‐CSF product (Neupogen, Amgen) has been used for many years for prevention and treatment of neutropenia and also for mobilization of peripheral blood stem cells (PBSCs). However, concerns have been raised about the safety and efficacy of biosimilar G‐CSF during PBSC mobilization procedures, especially in healthy donors. This article reviews the available evidence on the use of biosimilar G‐CSF in this setting. Aggregate clinical evidence supports the assessment by the EMA of biosimilar and originator G‐CSF as highly biologically similar, with respect to desired and undesired effects.